Solve, show all four steps. 3(x – 2) + 5(2x + 3) = 35 The steps are: Distribute Combine Like terms Add or subtract the constant Multiply or divide the get the variable alone.

QUESTION POSTED AT 16/04/2020 - 06:18 PM

Answered by admin AT 16/04/2020 - 06:18 PM

3x-6+10x+15=35
10x+3x=35-15+6
13x=26
x=2
Post your answer

Related questions

The expression 3 × 7 – 4 × 8 + 2 is equivalent

QUESTION POSTED AT 02/06/2020 - 01:42 AM

Graph the exponential function. y = 4(3) x

QUESTION POSTED AT 02/06/2020 - 01:30 AM